Bridging the Gap between Clients and Public Defenders: Introducing a Structured Shadow Method to Examine Attorney Communication - Campbell, Christopher M.; Henderson, Kelsey S. (The Justice system journal, 2022)
A growing body of scholarship argues that representing clients in an effective and quality manner should be a critical goal for public defenders, emphasizing the need to be client-centered. Beyond this call, recent research emphasizes that client-centered approaches hinge on good communication as it can contribute to a more effective attorney-client relationship. However, to identify and improve communication and client-centered relationships, major obstacles must be overcome which involve conceptualizing and operationalizing quality representation and communication. In this article, we introduce a two-phase, structured shadowing method as a way to overcome these obstacles. Phase I consists of a survey of public defenders that captures attorneys' perspectives of factors important in developing and maintaining good communication with clients. The second phase involves an exploratory method of shadowing attorneys in meetings with their clients, and administering a survey of clients to assess the importance of these factors from their vantagepoint and their overall perception of communication with their attorney. Additionally, we demonstrate how this method can be deployed to aid in understanding and improving attorney-client communication from both the attorneys' and clients' perspectives. We conclude the article with a discussion of how this method can help to progress research and practice related to quality representation, and as appendices we provide the tools used to demonstrate the approach.